2018
DOI: 10.1038/s41598-018-34735-7
|View full text |Cite
|
Sign up to set email alerts
|

Purified Inactivated Zika Vaccine Candidates Afford Protection against Lethal Challenge in Mice

Abstract: In response to the 2016 global public health emergency of international concern announced by the World Health Organization surrounding Zika virus (ZIKV) outbreaks, we developed a purified inactivated Zika virus vaccine (PIZV) candidate from ZIKV strain PRVABC59, isolated during the outbreak in 2015. The virus isolate was plaque purified, creating six sub-isolated virus stocks, two of which were selected to generate PIZV candidates for preclinical immunogenicity and efficacy evaluation in mice. The alum-adjuvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 58 publications
(61 reference statements)
0
35
0
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ to correlate with protection [23][24][25] . Further supporting this correlate of protection, it has been reported that passive transfer of Zika neutralizing monoclonal antibodies or antisera from vaccinated humans and animals to mice is sufficient to protect against ZIKV challenge 16,17,21,26 . Adoptive transfer of serum from immunized mice fully protected against viremia, while splenocytes from the same donors provided marginal protection 27 demonstrating that the mechanism of protection against ZIKV infection is antibody mediated.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…www.nature.com/scientificreports www.nature.com/scientificreports/ to correlate with protection [23][24][25] . Further supporting this correlate of protection, it has been reported that passive transfer of Zika neutralizing monoclonal antibodies or antisera from vaccinated humans and animals to mice is sufficient to protect against ZIKV challenge 16,17,21,26 . Adoptive transfer of serum from immunized mice fully protected against viremia, while splenocytes from the same donors provided marginal protection 27 demonstrating that the mechanism of protection against ZIKV infection is antibody mediated.…”
Section: Discussionmentioning
confidence: 83%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Neutralizing antibodies directed against the envelope (E) protein have been identified as correlates of protection for vaccines Japanese encephalitis virus (JEV), yellow fever virus, and tickborne encephalitis viruses 4 . Other laboratories using different vaccine platforms (DNA, RNA, inactivated virus, protein subunit, adenovirus-vectored, VLP) have reported induction of ZIKV-specific neutralizing antibodies that conferred protection against live ZIKV challenge in animal models [6][7][8][16][17][18][19][20][21][22] . These data support ZIKV E-specific neutralizing antibodies as a mechanism of protection against ZIKV infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations